2015
DOI: 10.1017/sjp.2015.27
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Drive for Thinness as a Perfectionistic Strategy to Escape from Shame Experiences

Abstract: Perfectionistic self-presentation defines the attempt at presenting the self as perfect through the public concealment of personal defects and/or through the display of attributes perceived as capable to gather positive attention of others. Although perfectionism has long been considered a central aspect of eating psychopathology mediational studies between this construct and these conditions are scarce. This study aimed at examining the mediational role of body image-related perfectionistic self-presentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
3
16
0
3
Order By: Relevance
“…This process resulted in the final sample of 487 female participants. [Ferreira et al, 2015]. This scale evaluates the need to present a perfect body image to others, by displaying a flawless physical appearance and occulting perceived body imperfections.…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…This process resulted in the final sample of 487 female participants. [Ferreira et al, 2015]. This scale evaluates the need to present a perfect body image to others, by displaying a flawless physical appearance and occulting perceived body imperfections.…”
Section: Participantsmentioning
confidence: 99%
“…In fact, several studies have shown that eating disorders' patients, when compared to nonclinical groups, report higher levels of shame even after treatment [16,19,21,22]. Additionally, literature suggests that pathological dieting and drive for thinness can function as a threat regulation strategy used to face shame [15,23]. Moreover, Ferreira et al [16] suggest that the control over weight or body shape may emerge as strategy to compete for social acceptance on women who present higher levels of external shame, and feel under pressure to attend to the social group's demands.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations